Dual Career of the U-23 Spanish Canoeing Team - Gavala-González, Juan; Castillo-Rodríguez, Alfonso; Fernández-García, José Carlos (Frontiers in Psychology, 2019)
Canoeing is one of the sport disciplines that brings great success to Spain in international competitions and OOGG (of the 17 medals won in Rio in 2016, four were in this sport). However, the journey to become an elite athlete coincides in time with the challenge of pursuing an academic education, which often involves making difficult choices in the training-university dichotomy. The present study was carried out with the Spanish under-23 flat water canoeing team, the step prior to competition at the highest level. The study sample comprised the whole population, namely the entire national team, made up of 20 athletes with a mean age of 20.55+2.31 years). These athletes are usually based at Cartuja High Performance Center (Seville) and combine their sports activity with studying towards a university degree. A double qualitative and quantitative methodology was used. For the first of these, an interview script was elaborated based on the theoretical model by Wylleman, Reints and de Knop (2013). Applicable consents were requested from the RFEP, coaches and paddlers. Interviews were carried out with each athlete twice: at the beginning and at the end of the season/academic year, which were recorded and subsequently tabulated and analyzed. Concerning quantitative methodology, the ESTPORT dual career questionnaire validated by Sánchez-Pato, et al (2016) was used. The results show that for all the paddlers canoeing is very important. It is typically complicated for them to attend classes, and subject planning is usually based on their training schedules. In the second/last part of the course, it is stressful for these athletes to combine both activities and some drop out of school. During the course, though, they appreciate having another activity that allows them to escape from the training routine. In addition, they miss not having an academic tutor to guide and advise them. These student-athletes are aware that their sport causes them to miss out on many moments with family and friends due to training or competing. However, at present this is offset, largely because of their high level of performance, which makes it easier for them to obtain scholarships that provide economic support.